1995
DOI: 10.1113/jphysiol.1995.sp020572
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II activation of a chloride current in rabbit cardiac myocytes.

Abstract: 1. The effects of angiotensin II (Ang II) on membrane currents were investigated in single ventricular myocytes from the rabbit heart by the whole-cell voltage-clamp method. 2. In the presence of an inhibitor of Ca2+ currents (nifedipine at 3 ,UM or CdCl2 at 0 3 mM) and a f6-adrenoceptor blocker (bupranolol at 1 /LM), 1 /uM Ang II significantly increased the membrane conductance.3. After elimination of K+ from external and internal solutions and its replacement by Cs+, Ang II at 041 /M increased an outwardly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
1
17
0
4
Order By: Relevance
“…Compared to phenylephrine, angiotensin II increased [ 14 C]phenylalanine incorporation less efficiently. Moreover, the concentration required to significantly stimulate protein synthesis (1 µM) was high compared to other physiological effects of angiotensin II, such as contraction [13], the induction of TGF-β expression [27], and the activation of chloride channels [12]. We conclude from the comparison of the concentration-response curves that the role of angiotensin II during the generation of myocardial hypertrophy is not a main effect on cardiac growth.…”
Section: Discussionmentioning
confidence: 94%
“…Compared to phenylephrine, angiotensin II increased [ 14 C]phenylalanine incorporation less efficiently. Moreover, the concentration required to significantly stimulate protein synthesis (1 µM) was high compared to other physiological effects of angiotensin II, such as contraction [13], the induction of TGF-β expression [27], and the activation of chloride channels [12]. We conclude from the comparison of the concentration-response curves that the role of angiotensin II during the generation of myocardial hypertrophy is not a main effect on cardiac growth.…”
Section: Discussionmentioning
confidence: 94%
“…In rabbit sinoatrial node cells, Ang II depolarized the RMPs accompanied by a reduction of the action potential amplitude and a negative chronotropic effect (23). In isolated rabbit ventricular myocytes, Morita et al (24) reported that Ang II decreased the APD after 3 min of application, but prolonged the APD after application for 7 min. These reports indicated that Ang II prolongation of the atrial and ventricular APDs was accompanied by membrane depolarization.…”
Section: Mechanism Of Ang Ii-induced Shortening Of the Atrial Action mentioning
confidence: 99%
“…118 Angiotensin II inhibits a number of K currents, including the Ca 2ϩ -activated K current in vascular smooth muscle cells, 119 the transient outward K current (I to1 ), 116 and delayed rectifier K currents in the heart and smooth muscle. 120 -125 Other direct effects of angiotensin II on cardiac membrane transport include increasing chloride current 112 and decreasing electrogenic Na ϩ -K ϩ ATPase. 126 The function of a number of ion channels and electrogenic transporters are regulated by aldosterone.…”
Section: Tomaselli and Zipes Sudden Death In Hf 757mentioning
confidence: 99%